Data from a large Western centre exploring the impact of COVID-19 pandemic on endoscopy services and cancer diagnosis. Issue 3 (30th July 2020) - Longcroft-Wheaton, Gaius; Tolfree, Natalie; Gangi, Anmol; Beable, Richard; Bhandari, Pradeep
Abstract : Objective: The global COVID-19 pandemic has changed healthcare across the world. Efforts have concentrated on managing this crisis, with impact on cancer care unclear. We investigated the impact on endoscopy services and gastrointestinal (GI) cancer diagnosis in the UK. Design: Analysis of endoscopy procedures and cancer diagnosis at a UK Major General Hospital. Procedure rates and diagnosis of GI malignancy were examined over 8-week periods in spring, summer and autumn 2019 before the start of the crisis and were compared with rates since onset of national lockdown and restrictions on elective endoscopy. The number of CT scans performed and malignancies diagnosed in the two corresponding periods in 2019 and 2020 were also evaluated. Results: 2 698 2516 and 3074 endoscopic procedures were performed in 2019, diagnosing 64, 73 and 78 cancers, respectively, the majority being in patients with alarm symptoms and fecal immunochemical test+ve bowel cancer screening population. Following initiation of new guidelines for management of endoscopy services 245 procedures were performed in a 6 week duration, diagnosing 18 cancers. This equates to potentially delayed diagnosis of 37 cancers per million population per month. Clinician triage improved, resulting in 13.6 procedures performed to diagnose one cancer. Conclusions: Our data demonstrate an 88% reduction in procedures during the first 6 weeks of COVID-19 crisis, resulting in 66% fewer GI cancer diagnoses. Triage changes reduced the number of procedures required to diagnose cancer. Our data can help healthcare planning to manage the extra workload on endoscopy departments during the recovery period from COVID-19.